A Glycosylation Mutant of Trypanosoma brucei Links Social Motility Defects In Vitro to Impaired Colonization of Tsetse Flies In Vivo - Imhof, Simon (Eukaryot Cell, 2015)
Transmission of African trypanosomes by tsetse flies requires that the parasites migrate out of the midgut lumen and colonize the ectoperitrophic space. Early procyclic culture forms correspond to trypanosomes in the lumen; on agarose plates they exhibit social motility, migrating en masse as radial projections from an inoculation site. We show that an Rft1(−/−) mutant needs to reach a greater threshold number before migration begins, and that it forms fewer projections than its wild-type parent. The mutant is also up to 4 times less efficient at establishing midgut infections. Ectopic expression of Rft1 rescues social motility defects and restores the ability to colonize the fly. These results are consistent with social motility reflecting movement to the ectoperitrophic space, implicate N-glycans in the signaling cascades for migration in vivo and in vitro, and provide the first evidence that parasite-parasite interactions determine the success of transmission by the insect host.